Beliefs and misperceptions about naloxone and overdose among U.S. laypersons: a cross-sectional study - Jon Agley; Yunyu Xiao; Lori Eldridge; Beth Meyerson; Lilian Golzarri-Arroyo (BMC, 2022)
Abstract Background Overdose education and naloxone distribution (OEND) to laypersons are key approaches to reduce the incidence of opioid-involved overdoses. While some research has examined attitudes toward OEND, especially among pharmacists and first responders, our understanding of what laypersons believe about overdose and naloxone is surprisingly limited. Further, some scholars have expressed concerns about the prevalence of non-evidence-based beliefs about overdose and naloxone. We designed this study to analyze the prevalence, nature, and context of beliefs about naloxone and overdose among U.S. laypersons. Methods We conducted a cross-sectional study (n = 702) using Prolific.co (representative of the U.S. population by age, gender, and race). Primary outcomes were the believability of six statements about overdose/naloxone on a seven-point Likert-type scale. Five statements were unsupported, and one was supported, by current scientific evidence. We used latent profile analysis to classify participants into belief groups, then used regression to study correlates of profile classification. Results Believability of the statements (7: extremely believable) ranged from m = 5.57 (SD = 1.38) for a scientifically supported idea (trained bystanders can reverse overdose with naloxone), to m = 3.33 (SD = 1.83) for a statement claiming opioid users can get high on naloxone. Participants were classified into three latent belief profiles: Profile 1 (most aligned with current evidence; n = 246), Profile 2 (moderately aligned; n = 351), and Profile 3 (least aligned, n = 105). Compared to Profile 1, several covariates were associated with categorization into Profiles 2 and 3, including lower trust in science (RRR = 0.36, 95%CI = 0.24-0.54; RRR = 0.21, 95%CI = 0.12-0.36, respectively), conservative political orientation (RRR = 1.41, 95%CI = 1.23-1.63; 3:RRR = 1.62, 95%CI = 1.35-1.95, respectively), and never being trained about naloxone (Profile 3: RRR = 3.37, 95%CI = 1.16-9.77). Conclusions Preliminary evidence suggests some U.S. laypersons simultaneously believe that bystander overdose prevention with naloxone can prevent overdose and one or more scientifically unsupported claims about naloxone/overdose. Categorization into clusters displaying such belief patterns was associated with low trust in science, conservative political orientation, and not having been trained about naloxone. Preregistration This cross-sectional study was preregistered prior to any data collection using the Open Science Framework: https://osf.io/c6ufv